Analysis of The Effect of Remittance on Economic Growth in Developing Countries East Asia and Pacific Region - Firdan Belado Romadona; Wisnu Wibowo; Hairul Rahman (MediaTrend, 2021)
This study determine how remittances affect economic growth in the developingcountries of East Asia and the Pacific region. The type of data in this study issecondary data with the form of panel data. This research was conducted in the period 2000-2019 in 11 developing countries in East Asia and the Pacific region. This study used Random Effect Model estimation to determine the influence ofindependent variables, namely GDP per capita with dependent variables, namelyremittances, working-age population, FDI, and trade openness. The result showsthat variable remittances and working-age populations positively and significantlyimpact economic growth in developing countries in East Asia and the Pacific region.The estimated results for FDI variables negatively and significantly affect developingcountries economic growth in East Asia and the Pacific region. Estimates for tradeopenness variables have no significant effect on developing countries economicgrowth in East Asia and the Pacific region.